E-097 Rapidly enlarging mycotic mca bifurcation aneurysm in patient with noonan's syndrome. (23rd July 2017) - Moore, N; Hardman, J; Cerejo, R; Wisco, D; Bain, M; Toth, G; Hussain, M
Abstract : Introduction: Noonan's syndrome is an autosomal dominant congenital disorder that often manifests as congenital heart defects including valvular defects and hypertrophic cardiomyopathy. Patients can manifest this syndrome with pterygium colli deformity (webbed neck) and blood clotting disorders. There have been multiple reports in the literature of a possible association with Moya Moya like disease. We discuss a patient who presented with endocarditis and heart failure and was found to have a rapidly enlarging right middle cerebral artery large bifurcation mycotic aneurysm in the setting of a vasculopathy. Case Description: The patient is a 33 year old female with a history of Noonan's syndrome, pulmonary artery aneurysm, mitral valve prolapse with streptococcus gordonii endocarditis that was complicated by decompensated heart failure. A cerebral angiogram was requested and demonstrated supraclinoid and M1 severe stenosis as well as a 5mm MCA bifurcation aneurysm with severely narrowed M2 branch origins. While the logistics for treatment for both the endocarditis and aneurysm were being planned, the patient developed sudden onset of a severe headache and was found to have subarachnoid blood on CT. A repeat angiogram was performed and the patient's aneurysm was found to have doubled in size within 4 days with a progressively dysplastic M1 segment becoming evident. Primary coiling was initiated to occlude the aneurysm as open surgery which would require bypass that would delay much needed heart surgery. The patient tolerated the procedure well and underwent heart valve replacement within a few days. Patient was discharged home in stable condition. Conclusion: Given the characteristic clinical phenotypes of patients with Noonen's syndrome, when presented with a patient suffering from endocarditis, a cerebral angiogram may be justified to rule out mycotic aneurysms and Moya Moya like disease. In this case, it is difficult to determine the etiology of the vasculopathy, as Noonen's syndrome has been associated with moya-moya like changes but an infective vasculopathy is also possible. The rapidly enlarging nature of this aneurysm is likely partially related to flow limitation of the distal vessel origins. Treatment by primary coiling can be considered as a viable treatment option for patient requiring open heart surgery for this situation. Disclosures: N. Moore: None. J. Hardman: None. R. Cerejo: None. D. Wisco: None. M. Bain: 2; C; Stryker Neurovascular. G. Toth: None. M. Hussain: None.